ANALISIS IMPLEMENTASI PRODUCT IMPROVEMENT INDUSTRI KREATIF DI KOTA MATARAM (STUDI TENTANG INDUSTRI KREATIF SEKTOR KERAJINAN DI KOTA MATARAM) - Septiani, Emilia (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
The economic value of a product is not only determined by the raw materials and production process, but it is also determined by creativity and innovation. Creative industry is one of the development concept based on creativity that could potentially increase the economic growth and social welfare. The concept of creative industry itself is creativity-based activities that affect the economy and welfare of the community, where the small industries such as handicrafts is currently widely scattered in various parts of Kota Mataram. The craft center located in Kota Mataram, are cukli, gold / silver, precious stones, weaving, pearl, songket, wood crafts / masks, craft souvenirs and many others. This craft has its own role in the development of the regional economy. The existence of product improvement and creativity that arise in the community makes the creative industries sector in Kota Mataram has an important role in the economic development of the city. The results showed that handicraft producers / entrepreneurs of cukli, gold-pearl, silver, and wood or mask in Kota Mataram has conducted product improvement in various aspects such as functional aspects, aspects of the form until the production aspects. There are several contributing factors for craft producers / entrepreneurs, namely the existence of venture capital assistance either from the bank, the government, even foreign capital; the availability of raw materials, and skilled labor. While the inhibiting factors include the difficulty to improve the quality if the workforce owned is not appropriate in terms of quality, technological limitations in the production process, and the instability of the economy that affect the purchasing power of producers / entrepreneurs to raw material quality. Keywords: Creative Industries, Craft Sector and Product Improvement